Scientific and engineering staff development for China transport industry - J. Zhang; N. M. Sheremet; I. G. Ovchinnikov; A. N. Steblyanskaya (Архитектура, строительство, транспорт)
The paper analyzes the policy and management experience of the China transport industry enterprises in the field of personnel talents development, as well as the results achieved in this direction. The authors evaluate the level of education, employment, unemployment, remuneration of specialists in transport industry. The paper studies the key problems faced in the course of training and personnel retraining in the China transport industry, and the possible causes of their occurrence. The primary research method is the "fish bone" method (a cause and effect diagram). In conclusion, the authors give recommendations how to optimize decision-making process necessary for the personnel sustainable development and the creation of talents teams in the China transport industry.